THE EFFECT OF CSR, FINANCIAL DISTRESS, AND GOOD CORPORATE GOVERNANCE ON STOCK RETURNS - Melinda, Puput; Hariyanto, Wiwit (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to determine and examine the effect of Corporate Social Responsibility (CSR), financial distress, and Good Corporate Governance (GCG) on stock returns in mining companies listed on the Indonesia Stock Exchange. Method: This study uses a quantitative method with secondary data as the main source. Stock return data was obtained from annual closing prices during the period 2021 to 2023. All information was then classified into research variables according to the needs of the analysis. The sample was determined using purposive sampling, which is a non-probability sampling method based on certain criteria relevant to the research objectives. Results: Based on the results of testing, analysis, and interpretation of data in this study, it can be concluded that Corporate Social Responsibility (CSR), financial distress, and Good Corporate Governance (GCG) have a significant effect on the stock returns of companies listed on the Indonesia Stock Exchange. Novelty: Theoretically, this study contributes to the understanding that the influence of CSR, financial distress, and corporate governance on stock returns is contextual, greatly influenced by industry characteristics, company financial conditions, and investor behavior in interpreting risk, profitability, and company sustainability. For investors, these results can be used as a reference in formulating investment strategies, considering that CSR does not always increase stock attractiveness, financial distress can open up opportunities for higher returns, and corporate governance, although important in the long term, can reduce returns in the short term.